Information-psychological security of society as a way of preserving nation - Грига, Владислав Сергеевич; Гнатюк, Сергей Александрович; Гизун, Андрей Иванович (Ukrainian Scientific Journal of Information Security, 2015)
The objects of information-psychological influence often are not only individuals, but also their groups, united by a certain feature. To one of these groups refers people (race) and nation. In this connection with the events of modern history when these influences come to a new stage of development, the subject of this work is definitely a relevant and important for the development of information security in general. In the study introduced the basic information-psychological impact concepts, discussed features of its implementation for the impact on society and the analysis of historical instances of such methods, by the example of the Ukrainian people, towards destruction, assimilation and absorption of Ukrainians. It was studied the history of Ukraine, which is conventionally divided into several historical periods: from Kievan Rus to 1569, from 1569 to 1795, from 1795 to 1917, from 1917 to 1991, and the period of independence and formation of Ukrainian state. Received results testify application of information-psychological impact methods from various external aggressors, throughout almost the entire lifetime of the Ukrainian people and nation, emphasize their commitment and consciousness. Also in the work carefully considered rewriting of history as one of the most common methods of forming appropriate beliefs, attitudes and philosophical principles in general.